Living in Multiple Worlds: Analyzing College Transitions and Dispositions through the Use of Critical Practice - Carrión, Alejandro E. (Journal of Latinos and education, 2023)
The academic progress and success of males of color have begun to capture the attention locally and nationally. Over the past several years research examining males of color and their k-12 to college, pathways have been the subject of conversation and focus of scholars and practitioners alike. This study examines the transition of successful Latino males and centers their perspectives through the analytical framework of Bourdieu's practice. This framework helps to theorize and capture strategies/logic/resistance male participants engaged in to shed stereotypical representations and stigmatized expectations placed on their bodies based on their identity as Latino males from the Bronx.